Genetic control of soybean resistance to race 4 of Cercospora sojina - Filho, Sebastião Martins; Gravina, Geraldo de Amaral; Sediyama, Carlos Sigueyuki (Pesquisa Agropecuaria Brasileira, 2002)
<!–[if gte mso 9]> Normal 0 <![endif]–> <!– /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; mso-ansi-language:PT-BR; @page Section1 size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.Section1 page:Section1; –> The objective of this work was to study the genetic control of resistance to frogeye leaf spot in segregating populations derived from the cross between Paraná and Bossier soybean cultivars. The progenitors and the F1, F2, RC1 and RC2 generations were evaluated for six plant characters associated to the disease: infection grade (NT); number of lesions per foliole (NLF); average diameter of lesion (DML); percentage of lesioned foliar area (PAFL); number of lesions per square centimeter (NLC) and disease index (ID). Soybean resistance to frogeye leaf spot behaved as a quantitative character, and the additive genic effect was the most important character. The influences on NT were the following: additive effect (62.05%), dominance effect (7.68%) and additive x additive, additive x dominant and dominant x dominant epistatic interactions (7.32%). The additive-dominant model was satisfactory to explain the variations only of PAFL and NLC characters. The influence of the effect of epistatic interactions varied from 2.22% for PAFL up to 30.78% for DML character. The additive-dominant genetic model is satisfactory to explain the behavior of the average of the generations of PAFL and NLC characters. However, for NT, NLF, DML and ID, the additive-dominant-epistatic model is more adequate